2022
DOI: 10.1007/s00402-022-04411-7
|View full text |Cite
|
Sign up to set email alerts
|

The radiographic outcome after plating for pubic symphysis diastasis: does it matter clinically?

Abstract: Introduction Open reduction and internal fixation with plates is the most widespread surgery in traumatic pubic symphysis diastasis. However, implant failure or recurrent diastasis was commonly observed during follow-up. The aim of our study was to evaluate the radiologic findings and clinical outcomes. Materials and methods Sixty-five patients with traumatic pubic symphysis diastasis treated with plating between 2008 and 2019 were retrospectively reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
2
5
2
Order By: Relevance
“…The Majeed Pelvic Score was higher in the implant failure group after adjusting it to the previous work of patients. The implant failure rate of 37% is comparable to previous reports [ 12 , 15 , 18 , 19 ]. Furthermore, the median time to implant failure of approximately 10 weeks is comparable to Rojas et al (seven weeks), Eastman et al (13 weeks) and Avilucea (16 weeks) et al but earlier than reported by Morris et al (one year) [ 5 7 , 12 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The Majeed Pelvic Score was higher in the implant failure group after adjusting it to the previous work of patients. The implant failure rate of 37% is comparable to previous reports [ 12 , 15 , 18 , 19 ]. Furthermore, the median time to implant failure of approximately 10 weeks is comparable to Rojas et al (seven weeks), Eastman et al (13 weeks) and Avilucea (16 weeks) et al but earlier than reported by Morris et al (one year) [ 5 7 , 12 ].…”
Section: Discussionsupporting
confidence: 86%
“…As in the study of Frietman et al no predictors of implant failure in patients’ demographics could be detected [ 15 ]. Tseng et al reported, that males suffer more often from implant failure [ 19 ]. Due to the gender inhomogeneity of the cohort presented here, with 93% male patients, this finding could either be proven or disproven.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the adductor muscles and hamstring muscles could be reattached anatomically, ensuring better functional recovery and pain improvement. However, the natural pubic symphysis permits a minute shift of 2 mm and 1° of rotation, which prevents stress fracture under peak loading ( Hammer et al, 2019 ; Tseng et al, 2022 ). After rigid prosthetic reconstruction of region III, the pubic symphysis bore greater vertical deformation than the other parts ( Dong et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are certain challenges depending on the patient profile, pattern of fractures and degree of displacement. Although it is one of the easier surgeries, there are often high failure rates, mostly due to the backout of screws and eventual implant failure which necessitates resurgery 2–4. Morbid obesity makes the otherwise simple surgery quite challenging due to difficult exposure and reduction, requirement of working at a depth and difficulties in screw trajectory due to pendulous abdomen 5–11.…”
Section: Introductionmentioning
confidence: 99%